Optimizing the preparation and stability of decorated antiretroviral drug nanocrystals. (19th March 2018) - Zhou, Tian; Lin, Zhiyi; Puligujja, Pavan; Palandri, Diana; Hilaire, James; Araínga, Mariluz; Smith, Nathan; Gautam, Nagsen; McMillan, JoEllyn; Alnouti, Yazen; Liu, Xinming; Edagwa, Benson; et al.
Aim: While the  therapeutic potential for current long-acting (LA) antiretroviral therapy (ART) is undeniable, ligand-decorated nanoformulated LA-ART could optimize drug delivery to viral reservoirs. The development of decorated ART hinges, however, on formulation processes and manufacture efficiencies. To this end, we compared manufacture and purification techniques for ligand-decorated antiretroviral drug nanocrystals.Materials & methods: Ligand-decorated nanoparticle manufacturing was tested using folic acid (FA) nanoformulated cabotegravir.Results: Direct manufacturing of FA-cabotegravir resulted in stable particles with high drug loading and monocyte–macrophage targeting. A one step 'direct' scheme proved superior over differential centrifugation or tangential flow filtration facilitating particle stability and preparation simplicity and efficiency.Conclusion: Direct manufacturing of FA nanoparticles provides a path toward large-scale clinical grade manufacturing of cell-targeted LA-ART. Lay abstract: Folic acid (FA) decoration on the surface of nanocrystals can be achieved by mixing FA conjugated poloxamer 407 (FA-P407) and native P407 in varied ratios followed by size reduction by homogenization and differential centrifugation or tangential flow filtration to remove excess unbound polymers. The optimized manufacturing scheme is by direct homogenization with predetermined quantity of FA conjugated P407. Direct manufacturing method yields stable homogenous nanoparticles with high drug loading.